Studies of Level of Service (LOS) at Signalized Intersection With Mix Traffic Flow - Alvisyahri, Alvisyahri; Malia, Rezqi; Dinda, Raina Parmitalia; Idris, Fadli; Rahman, Aulia; Tripoli, Bambang; Farizal, Teuku (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2023)
One of the signalized intersections with four approaches is the BPKP’s intersection at Banda Aceh.  The intersection will be analyzed in the current condition and remodeled using the software SIDRA intersection 8.0. This Software can choose a predetermined minimum capacity for each little movement. Utilizing a video from a collected in the study area, the institute provided the information. Data from a video included vehicle volume, downstream distances, upstream distances, and negotiation distances, as well as transit time. in its current condition. The total flow of demand is 1060 pcu/h. degree of saturation is 1,406, and level of service is F. The remodel of this intersection is analyze the signalized intersection's traffic light cycle time. It is necessary to be able to handle the current that enters the intersection. Total flow of demand in remodel condition of BPKP's intersection at Banda Aceh is 1060 pcu/h, degree of saturation is 0,765, and level of service is C.